The social structure, distribution and demographic status of the African elephant population in the Central Limpopo River Valley of Botswana, Zimbabwe and South Africa - Van Hoven, Wouter (University of Pretoria, 2013)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 2008.